A more equal world? An analysis of the global inequality trends in the period 2000-2020 - Arthur Zito Guerriero (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This paper analyzes the evolution of global interpersonal income inequality in the last decades. While some authors emphasize that global inequality fell significantly between 2000 and 2020 (Milanovic, 2024), others argue that global inequality has remained constant (Chancel & Pikey, 2021) or even increased (Hickel, 2017). This paper contributes to the interpretation of this period by showing that while global inequality did fall between 2000 and 2020, this trend was not the result of a truly global convergence process involving all countries, as it was mainly driven by high growth rates in Asia. Combining data from the World Income Inequality Database (WIID) with population forecasts from the United Nations, an upward trend in global income inequality is projected, even if the economic shocks of COVID-19 and the invasion of Ukraine are not taken into account. The present study shows that a significant share of the Chinese population has reached such high-income levels that further increases in these incomes will contribute to a rise in inequality. Moreover, a further reduction in global inequality will require faster income growth in sub-Saharan Africa and South Asia, whereas sustained high growth rates in East Asia will contribute to higher inequality. – – In diesem Beitrag wird die Entwicklung der globalen interpersonellen Einkommensungleichheit in den letzten Jahrzehnten analysiert. Während einige Autoren betonen, dass die globale Ungleichheit zwischen 2000 und 2020 deutlich gesunken ist (Milanovic, 2024), argumentieren andere, dass die globale Ungleichheit konstant geblieben ist (Chancel & Pikey, 2021) oder sogar zugenommen hat (Hickel, 2017). Das vorliegende Papier trägt zur Interpretation dieses Zeitraums bei, indem es zeigt, dass die globale Ungleichheit zwischen 2000 und 2020 zwar gesunken ist, dieser Trend aber nicht das Ergebnis eines wirklich globalen Konvergenzprozesses war, der alle Länder einbezog, da er hauptsächlich durch hohe Wachstumsraten in Asien angetrieben wurde. Kombiniert man die Daten der World Income Inequality Database (WIID) mit den Bevölkerungsprognosen der Vereinten Nationen, so wird ein Aufwärtstrend der globalen Einkommensungleichheit prognostiziert, selbst wenn die wirtschaftlichen Schocks von COVID-19 und die Invasion in der Ukraine nicht berücksichtigt werden. Die vorliegende Studie zeigt, dass ein erheblicher Teil der chinesischen Bevölkerung ein so hohes Einkommensniveau erreicht hat, dass ein weiterer Anstieg dieser Einkommen zu einem Anstieg der Ungleichheit beitragen wird. Darüber hinaus erfordert eine weitere Verringerung der globalen Ungleichheit ein schnelleres Einkommenswachstum in Afrika südlich der Sahara und in Südasien, während anhaltend hohe Wachstumsraten in Ostasien zu einer höheren Ungleichheit beitragen werden.
Keywords: D30; D31; 330; Global inequality; income distribution; China; convergence; projection